2017
DOI: 10.1021/acs.biochem.7b00815
|View full text |Cite
|
Sign up to set email alerts
|

Fluorotryptophan Incorporation Modulates the Structure and Stability of Transthyretin in a Site-Specific Manner

Abstract: Abnormal deposition of aggregated wild-type (WT) human transthyretin (TTR) and its pathogenic variants is responsible for cardiomyopathy and neuropathy related to TTR amyloidosis. The tryptophan (Trp) fluorescence measurements typically used to study structural changes of TTR do not yield site-specific information on the two Trp residues per TTR protomer. To obtain such information, tryptophan labeled with fluorine at the 5 and 6 positions (5FW and 6FW) was incorporated into TTR. Fluorescence of 5FW and 6FW-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 72 publications
(221 reference statements)
3
34
0
Order By: Relevance
“…S1. The translational diffusion coefficient of C10S-S85C was measured on the 900-MHz spectrometer using 15 N-filtered DOSY at pH 7.0 and 298 K. The measured translational diffusion coefficient is (5.1 ± 0.1) × 10 −7 cm 2 /s for C10S-S85C, which agrees with the reported data of WT TTR as (5.1 ± 0.2) × 10 −7 cm 2 /s (46). BTFA labeling is site-specific to S85C because the observed tetramer 19 F peak at −84.19 ppm in TTR F at 298 K is absent in a C10S control that was treated with BTFA the same way as C10S-S85C (SI Appendix, Fig.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…S1. The translational diffusion coefficient of C10S-S85C was measured on the 900-MHz spectrometer using 15 N-filtered DOSY at pH 7.0 and 298 K. The measured translational diffusion coefficient is (5.1 ± 0.1) × 10 −7 cm 2 /s for C10S-S85C, which agrees with the reported data of WT TTR as (5.1 ± 0.2) × 10 −7 cm 2 /s (46). BTFA labeling is site-specific to S85C because the observed tetramer 19 F peak at −84.19 ppm in TTR F at 298 K is absent in a C10S control that was treated with BTFA the same way as C10S-S85C (SI Appendix, Fig.…”
Section: Methodssupporting
confidence: 85%
“…Protein Expression, Purification, and Labeling. TTR mutants were expressed as described previously (46). See SI Appendix for details of protein purification and labeling.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the results of the current study revealed, for the first time, that preoperative TTR was an independent prognostic factor for 5-year recurrence-free survival in NSCLC patients. The normal function of TTR is to transport thyroxine and RBP/retinol complex in the blood (14). TTR exists in the blood as a homotetramer and contains four tryptophans which are essential amino acids (5).…”
Section: Discussionmentioning
confidence: 99%
“…Such mixtures may be readily achieved by mixing of different isoforms or through providing multiple fluoroindole precursors during biosynthesis. The value of applying F‐Trp mixtures also follows from dramatically different 19 F chemical shift dispersion for 5F‐ versus 6F‐Trp for the two native Trp residues of transthyretin, exhibiting distinct sensitivity to environment despite unperturbed folding, as well as a greater 4F‐Trp chemical shift dispersion versus 5F‐ or 6F‐Trp in lysozyme . Multi‐site perturbation should, therefore, be straightforwardly and efficiently tracked by 1D 19 F NMR experiments following multiple F‐Trp types instead of relying upon a single F‐Trp type which may or may not be an effective probe in all conditions.…”
Section: Figurementioning
confidence: 99%
“…In summary, mixtures of membrane protein isoforms that contain differently‐substituted F‐Trp residues at each Trp position were readily biosynthesized. Although the focus here has been on 19 F NMR spectroscopy, it should also be noted that the modified photophysics of F‐Trp versus Trp residues imply broader applicability of these approaches for fluorescence spectroscopy and resonance energy transfer characterization. Both 19 F chemical shift and spin dynamics were consistent between AR constructs as a function of position.…”
Section: Figurementioning
confidence: 99%